Asset Recovery Handbook : A Guide for Practitioners - Brun, Jean-Pierre; Gray, Larissa; Scott, Clive; Stephenson, Kevin M. (World Bank, 2012)
The handbook is organized into nine chapters, a glossary, and ten appendixes of additional resources. Chapter one provides a general overview of the asset recovery process and legal avenues for recovery, along with practical case examples. Chapter two presents a host of strategic considerations for developing and managing an asset recovery case, including gathering initial sources of facts and information, assembling a team, and establishing a relationship with foreign counterparts for international cooperation. Chapter three introduces the techniques that practitioners may use to trace assets and analyze financial data, as well as to secure reliable and admissible evidence for asset confiscation cases. The provisional measures and planning necessary to secure the assets prior to confiscation are discussed in chapter four; and chapter five introduces some of the management issues that practitioners will need to consider during this phase. Confiscation systems are the focus of chapter six, including a review of the different systems and how they operate and the procedural enhancements that are available in some jurisdictions. On the issue of international cooperation, chapter seven reviews the various methods available, including informal assistance and mutual legal assistance requests; and guides practitioners through the entire process. Finally, chapters eight and nine discuss two additional avenues for asset recovery-respectively, civil proceedings and domestic confiscation proceedings undertaken in foreign jurisdictions.